Modeling the evolution of SIV into HIV using humanized mice - Boddeda, Srinivasa Rao, author; Akkina, Ramesh, advisor; Laybourn, Paul, committee member; Juarrero, Mercedes Gonzalez, committee member; Ryan, Elizabeth, committee member (Colorado State University. Libraries, 2016)
Acquired Immunodeficiency syndrome (AIDS) is caused by two lentiviruses belonging to the family Retroviridae, namely HIV-1 and HIV-2, which originated from SIVcpz and SIVsmm respectively. Multiple independent cross-species transmission events of SIV from chimpanzees (SIVcpzPtt ) and gorillas (SIVgor) have given rise to four groups of HIV-1 (M, N, O, P), while transmission from sooty mangabeys (SIVsmm) is responsible for at least 8 groups of HIV-2 (A-H) (Ayouba et al., 2013; Gao et al., 1999; Hirsch et al., 1989). Some of these groups are extremely rare. However, four have established themselves in human populations as pandemic (HIV-1 group M) or epidemic (HIV-1 group O, HIV-2 groups A and B) outbreaks (Faria et al., 2014). While these data suggest that SIV transmission to a human host is by itself not sufficient to establish a new epidemic outbreak, it also implies that viral adaption is necessary for efficient spread of the virus within humans (Marx et al., 2004). However, exact role of factors such as immune selective pressure and genomic changes, contributed to successful SIV adaptation in humans remains unclear. Study of SIV transmission to humans has been limited by lack of an appropriate model. Ethical constraints prevent experimental challenge of human subjects with SIV and transmission studies have thus far been limited to non-human primates (NHPs) (Chahroudi et al., 2012). While NHP studies have been instrumental to identify key differences in innate and adaptive immune responses that influence transmissibility and virulence of SIV between species, until now experimental in vivo challenge of a functional human immune system with SIV has not been possible. Recently however, a new generation of humanized Rag2−/−γc−/− mice has been established that supports systemic engraftment of a functional human immune system (Akkina, 2013; Denton et al., 2012). These animals are susceptible to HIV-1 infection by mucosal routes and display key features of pathogenic HIV-1 infection in humans, including sustained plasma viremia, CD4+ T cell depletion and increased levels of immune exhaustion markers (Berges et al., 2006; Palmer et al., 2013). Additionally, humanized mice are able to mount adaptive immune responses to HIV-1 infection, producing antibodies and HIV-1 specific T cell responses. In the current study, we used humanized Rag2−/−γc−/− mice to study SIV transmission to humans. We hypothesized that humanized mice could support SIV infection, and that the presence of in vivo selective pressures, either innate or adaptive, would drive viral evolution. That is, we expected the majority consensus virus emerging in the plasma of productively infected humanized mice different from the stock virus used to infect the animals. Viral adaptation within infected humanized mice could produce a variant virus more fit for growth and transmission in humans. We infected humanized mice with both SIVsmmE041 and SIVcpzLB715 isolates and measured plasma viral loads and determined complete viral genome sequences. Both SIVsmm and SIVcpz showed stable viral loads over time for up to 7 months. SIVsmm virus from the infected mice was successfully passaged to three successive generations of humanized Rag2−/−γc−/− mice via intraperitoneal route. We were also able to show that human cell-adapted SIVsmm can infect humanized mice through the mucosal route. Sequence analyses of SIVsmm and SIVcpz output virus from these mice showed many functional mutations in various genes such as Gag, Pol, Env, Vif, Vpx, Vpr and Nef regions. In both viruses, Env regions showed the highest number of mutations suggesting that the envelope region of this virus might be under selective pressure for this virus to be able to replicate in human cells. We observed that the number of mutations in all genes increased over time, suggesting that the SIVsmm virus is continuously evolving and adapting for successful replication and transmission in these humanized mice. These studies will provide a flexible in vivo model for elucidating the mechanisms underlying SIV transmission and gain of function to replicate in humans.